Effect of dietary supplementation with oregano oil premix on the antioxidant status, performance, and meat quality in slow-growth broiler chickens - Evgenia Fotou; Vasiliki Moulasioti; Dimitra Kyriakou; Maria-Eleni Boti; Vassilios Moussis; Maria Papadami; Constantinos Tellis; Apostolos Patsias; Ioannis Sarrigeorgiou; Georgios A. Papadopoulos; Peggy Lymberi; Vasileios Tsiouris; et al. (Italian Journal of Animal Science)
This study investigated the influence of dietary supplementation with oregano oil premix on the antioxidant status, performance, and meat quality of slow-growth genotype chickens raised under a commercial production system. The study included two groups, with nine replicates: Group A) 54.000 broilers raised in free-range farms and fed the basal diet, and Group B) 27.000 broilers raised in free-range farms and fed the basal diet supplemented with oregano oil premix. Oregano oil was blended with a standard premix (120 g/ton), which was then mixed with the feed (amount adjusted on the growth stage). The results showed that serum total antioxidant capacity (TAC) was significantly higher (p ≤ 0.05) in the non-supplemented group compared to the dietary-supplemented group with oregano oil premix. In contrast, thigh muscle total antioxidant capacity was significantly increased in the supplemented group compared to the non-supplemented group (p ≤ 0.05). There were no differences in serum and thigh muscle Thiobarbituric Acid Reactive Substances (TBARS) and performance parameters between the two groups. Chickens fed with the oregano oil premix exhibited increased protein and ash content, pH value, and higher smell, taste, and colour scores compared to the non-supplemented group. Summarising, our large-scale in field study showed that incorporating oregano oil premix in slow-growth and free-range chickens’ diet improves the thigh muscle total antioxidant capacity and meat quality. The results indicate that the oregano oil premix positively impacts the nutritional value of the final product. However, more research is needed under in field conditions to draw a safer conclusion.